2015
DOI: 10.1177/2150135115586814
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury and Fluid Overload in Neonates Following Surgery for Congenital Heart Disease

Abstract: To avoid increased risk of morbidity and possibly mortality, every attempt should be made to identify and intervene on those risk factors, which may be modifiable or identifiable preoperatively, such as small kidneys by renal ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1
9

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 25 publications
2
42
1
9
Order By: Relevance
“…Higher RACHS category was found to be associated with AKI by Piggott et al; however in the current study this was not found to be significant. 22 Even though AKI tends to occur more commonly in procedure with higher RACHS score and higher Aristotle score. Younger age has been associated with higher risk of AKI in previous reports; no significant difference could be found in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher RACHS category was found to be associated with AKI by Piggott et al; however in the current study this was not found to be significant. 22 Even though AKI tends to occur more commonly in procedure with higher RACHS score and higher Aristotle score. Younger age has been associated with higher risk of AKI in previous reports; no significant difference could be found in the study.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11]17,21 We found prolonged CPB time to be associated with higher odds of developing AKI which was consistent with previous studies. [9][10][11]21,22 The possible reason of longer CPB time associated with AKI is multifactorial and probably due to the physiological alternation occurring during CPB. 20 In the study higher AXC time was found to be significantly associated with AKI.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, pediatric CS-AKI has been consistently associated with a number of complications including increased morbidity and mortality in this population. In the short term, after adjustment for covariates, pediatric CS-AKI is independently associated with longer duration of ventilation, longer intensive care unit and hospital stay, increased inotropic support, increased occurrence of low cardiac output syndrome, and increased mortality [1,3,1219]. In the long term, severe pediatric CS-AKI is independently associated with increased mortality [3,15], lower z-score for height [15], as well as evidence for chronic kidney disease [20].…”
Section: Incidence and Etiology Of Cardiac Surgery-associated Acutmentioning
confidence: 99%
“…Postoperative acute kidney injury (AKI) in pediatric patients is a serious complication associated with adverse outcomes including prolonged mechanical ventilation, prolonged hospital stay, and high morbidity and mortality [17]. Previous studies have reported that younger age [1, 3, 4, 7], prematurity [4, 6], longer cardiopulmonary bypass (CPB) time [24, 6, 7], a high Risk Adjusted Classification of Congenital Heart Surgery (RACHS-1) score [1, 7], longer vasopressor use [3] and selective cerebral perfusion [8, 9] are associated with CS-AKI in infants and children. Recently, several plasma and urine biomarkers reflecting renal injury have been investigated to facilitate early diagnosis [1012].…”
Section: Introductionmentioning
confidence: 99%